2018
DOI: 10.1111/1756-185x.13328
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of cardiovascular events in polymyalgia rheumatica and giant cell arteritis amongst an Asian population: Propensity score matched cohort study

Abstract: Patients with PMR or GCA may not have a higher risk of future cardiovascular diseases among the Japanese population. The sensitivity analyses and sample size calculation supported the results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…In PMR, data on the risk of coronary artery 171 and peripheral vascular 172 disease seem to be controversial: although some studies reported an increased risk in patients with PMR, others found the risk to be comparable with that of the general population 173,174 . Patients with PMR should therefore receive cardiovascular management on the basis of their individual risk profile.…”
Section: Disease and Treatment Complicationsmentioning
confidence: 99%
“…In PMR, data on the risk of coronary artery 171 and peripheral vascular 172 disease seem to be controversial: although some studies reported an increased risk in patients with PMR, others found the risk to be comparable with that of the general population 173,174 . Patients with PMR should therefore receive cardiovascular management on the basis of their individual risk profile.…”
Section: Disease and Treatment Complicationsmentioning
confidence: 99%
“…Furthermore, a meta-analysis of observational high-quality studies that included 34,569 patients with PMR showed a 72% excess risk of coronary artery disease among patients with PMR compared with subjects without PMR, even if the statistical heterogeneity of the reviewed studies was high 26 . Conversely, in a recent study, patients with PMR or GCA did not have a high risk for cardiovascular disease, but we must remark that the setting was Japan population, having the lowest incidence of PMR in the world and milder symptoms than in the Western countries 27 . The association of PMR with vascular disease may be explained by the elevated levels of C-reactive protein, which is also one of the independent biomarkers associated with cardiovascular disease 28 .…”
Section: Discussionmentioning
confidence: 63%
“…While GCA is a major comorbidity in patients with PMR, it is 20 times less common in Asian populations compared with Caucasian patients. 34,35 This study represents only the characteristics of Asian patients with PMR. In addition, we reviewed the clinical data retrospectively, so the data from some patients were missing.…”
Section: Discussionmentioning
confidence: 99%
“…29 Patients with migraine, a primary form of headache, had higher platelet counts and lower platelet membrane fluidity or activity compared with controls. 34,35 This study represents only the characteristics of Asian patients with PMR. 32,33 Whether a patient with PMR reaches remission or continues with This study had several limitations due to the research method and the study population.…”
Section: Clinical Characteristics Including the Levels Of Nlr Plrmentioning
confidence: 99%